Եւրատեսիլ երգի մրցոյթը Հայաստանում - Պատալեան, Տաթեւ (տպ. Atlas)
The Eurovison song contest is a world -renowned musical contest that started in 1956 with a handful of European states. In time the number of participating states grew and included not only European countries but countries like Armenia, Georgia, Israel and Azerbaijan. The paper notes that one of the main obje ctives of the contest organizers was to establish a forum where different cultures meet and the diversity of music and its acceptance by all is promoted. The paper narrates how the contest grew and developed, it examines the by -laws adopted that shaped and reshaped certain aspects of the contest, like the number of participants of each country on the stage, the duration of the songs, lyrics and language, the voting system and process, the stage and performance particularities (decoration, background music, etc.). The author focuses on the participation of the Republic of Armenia, which joined the song contest in 2006. She details the selection process of the Armenian participants, the body that is in charge, the Armenian singers and groups who have participated, the songs they have sung , the domestic and international challe nges they have faced, and their achievements. The author und erlines the fact that it is not a mere musical contest where the lyrics, or the composition, or the performance are taken into consideration, but a combination of these as well as the costumes the performers wear, the stage decoration, the answers the participants come up with during interviews, the musical instruments, the content of the introduction to each state and the way it is presented, etc. The author notes that the contest is a great opportunity to introduce the participating countries to a large audience - the character istic and peculiar features of the countries, their nature, culture and history. The author notes that after almost 2 decades of participation, Armenia needs to establish a wise policy and see the ch allenges it faces in order to have better results. The author notes that for that objective certain guidelines should be further developed, and that a group -think, collaborative mode might be more helpful and successful than the guidelines that have been in use so far.
Keywords: Եւրատեսիլ; Հայաստան